Detecção, quantificação e transmissão de xanthomonas citri subsp. malvacearum em sementes de algodão - Tumelero, Andréia Iraci (2012)
One of the factors responsible for yield losses of cotton (Gossypium hirsutum L.) is the occurrence of diseases. The angular leaf spot incited by Xanthomonas citri subsp. malvacearum is a disease whose control is accomplished primarily through resistant cultivars and pathogen free seeds. The seeds are one of the most important sources of spread of this pathogen. In Brazil, do not always make use of certified seeds for the establishment of crops, causing the occurrence of epidemics. This study aimed to promote improved health of cotton crops by evaluating methods and techniques for 3 detection, identification and quantification of X. citri subsp. malvacearum (Xcm) in cotton seeds. The following factors were evaluated, improved and/or validated microbiological methods. Cotton seed naturally and artificially contaminated by microbiological methods were evaluated using culture media semi-selective in the literature, as well as ways of extraction for the detection of this bacterium were evaluated. Seeds spiked/infected planting were subjected to studies for transmission of the bacteria to plant seeds. This study was conducted in laboratory and greenhouse. The results allow to define the culture media and PSA + 523 modified as that provided the development of Xcm high uniformity regardless of types of seed inoculation. In assessing the commercial seed from different states of the country, the presence of Xcm was seen in five of a total of twenty-three samples tested was not possible to quantify the pathogen by dilution and plating in the culture medium. From these samples were isolated seed bacteria Xanthomonas citri subsp. malvacearum, Pantoea agglomerans and Curtobacterium flaccumfaciens, which caused hypersensitivity reactions in tobacco leaves and pathogenicity on cotton plants. The transfer of bacteria to plant seeds from artificially contaminated seeds was between 0.016 to 0.15%. The resistance of plant genotypes of cotton or the aggressiveness of the bacteria may influence these results. This also confirms the difficulty to correlate the different levels of contamination of the seeds with the number of plants that express the disease